A near-infrared polymer enables over 50% transmittance in semi-transparent organic solar cells. Issue 15 (18th March 2022) - Wei, Qingyun; Zhang, Yi; Shan, Tong; Zhong, Hongliang
Abstract : A semi-transparent organic solar cell achieves an over 50% average visible transmittance, which is attributed to the rational design of the polymer donor with extended absorption in the near-infrared region. Abstract : Semi-transparent organic solar cells (ST-OSCs) have shown great potential for integration into the windows of buildings. An absorption region that is dominated by photovoltaic materials is vital for ST-OSCs. However, the state-of-the-art polymer donors are not specially tailored for ST-OSC applications and have a strong absorption in the visible region. Therefore, two polymers, namely 44-PTB and 66-PTB, are rationally designed by combining a benzodithiophene and two fluorinated thienothiophenes (FTT) in the repeat unit. Benefiting from the donor–acceptor–acceptor (D–A–A) configuration, the intramolecular charge transfer (ICT) effect is thus enhanced to red-shift the absorption of the corresponding polymers. Meanwhile, the regioregularity caused by the asymmetric structure of the FTT significantly affects the molecular geometry of these polymers. Compared with 44-PTB, 66-PTB with a more planar skeleton has a bathochromic and strong absorption in the near-infrared (NIR) region, which is conducive to improving the photon harvest and transmittance. In addition, the relatively planar backbone helps 66-PTB to achieve better intermolecular packing and form a fibrous structure in the film. As the result, the opaque device based on 66-PTB achieved a PCE of 7.84%, while the PCE of the device based on 44-PTB is only 5.93%. More importantly, ST-OSCs based on 66-PTB realize an average visible transmittance (AVT) as high as 50.82% accompanied by a PCE of 5.11%, which is among only a few ST-OSCs with a >50% AVT. The color rendering index (CRI) is 74.09, and the colour coordinates are (0.294, 0.338), which are meet the requirements of windows used in civil architecture.